2020
DOI: 10.1021/jacs.9b12464
|View full text |Cite
|
Sign up to set email alerts
|

Increasing the Cytotoxicity of Ru(II) Polypyridyl Complexes by Tuning the Electronic Structure of Dioxo Ligands

Abstract: Due to the great potential expressed by an anticancer drug candidate previously reported by our group, namely, Ru-sq ([Ru(DIP)2(sq)](PF6) (DIP: 4,7-diphenyl-1,10phenanthroline, sq: semiquinonate ligand), we describe in this work a structure-activity relationship (SAR) that involves a broader range of derivatives resulting from the coordination of different catecholate-type dioxo ligands to the same Ru(DIP)2 core. More in detail, we chose catechols carrying either electron-donating or electronwithdrawing groups… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
57
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 53 publications
(59 citation statements)
references
References 101 publications
2
57
0
Order By: Relevance
“…Some of these and related systems have been altered further by introducing a central metal ion into the tetrapyrrolic scaffold to enhance the chemical, photophysical, and biological characteristics of the parent PSs. [29,30] Design of the next generation of PSs has been focused on extending the absorption window to include NIR wavelengths (700-900 nm) [31][32][33][34] and to alter the excited state properties of the molecules to exploit oxygen-independent mechanistic pathways to achieve phototoxic effects in hypoxia. [35][36][37][38][39][40] Ru II polypyridyl complexes are particularly attractive scaffolds for PS design because the photophysics of these complexes is wellestablished [41][42][43][44][45][46][47] and polypyridyl ligand combinations can be chosen to systematically manipulate the excited state dynamics in a rational and consistent manner.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Some of these and related systems have been altered further by introducing a central metal ion into the tetrapyrrolic scaffold to enhance the chemical, photophysical, and biological characteristics of the parent PSs. [29,30] Design of the next generation of PSs has been focused on extending the absorption window to include NIR wavelengths (700-900 nm) [31][32][33][34] and to alter the excited state properties of the molecules to exploit oxygen-independent mechanistic pathways to achieve phototoxic effects in hypoxia. [35][36][37][38][39][40] Ru II polypyridyl complexes are particularly attractive scaffolds for PS design because the photophysics of these complexes is wellestablished [41][42][43][44][45][46][47] and polypyridyl ligand combinations can be chosen to systematically manipulate the excited state dynamics in a rational and consistent manner.…”
Section: Introductionmentioning
confidence: 99%
“…Various Ru II -based NIR scaffolds are known, but their phototoxic effects on cells were not reported. [31][32][33][34]50] Generally, the 1 O 2 quantum yields are low (and PDT effects thus poor) for metal complexes with lowenergy triplet metal-to-ligand charge transfer ( 3 MLCT) excited states due to efficient intersystem crossing (ISC) that competes effectively with 1 O 2 sensitization. [46] To circumvent this issue, we aimed to design Ru II -based NIR complexes with 3 ILCT states that are lower in energy than the 3 MLCT states and much longer lived, due to their organic 3 ππ* character.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…63 That an evidently different clearance pathway is used by [ 111 In][In-2] 4+ is particularly interesting considering the interest in RPCs as alternative therapeutics to platinum drugs and also the fact that clinical use of cisplatin is limited by nephrotoxicity. 64 We also note with interest that high liver uptake was reported for a hydrophobic mononuclear RPC by the Gasser group, 65 indicating this may be a general outcome for RPCs. Chemical rerouting of an elimination pathway towards hepatic clearance will aid further design of RPCs as nonplatinum chemo/radiotherapeutics, and indicates that hepatotoxicity may be a concern for this class of chemical.…”
Section: Discussionmentioning
confidence: 67%
“…The with hydrophobic ancillary ligands such as DIP (DIP ¼ 4,7diphenyl-1,10-phenanthroline) could increase cellular uptake, related research has shown this approach leads to a decrease in nuclear DNA targeting 30,66 and results in potentbut non-speciccytotoxicity. 65 Instead, a delivery mechanism may be a more appropriate method to achieve sufficient tumour uptake in vivo for the therapeutic potential of this molecule to be assessed in more detail. One attractive option is bioconjugation employing a cleavable linker to a peptide or antibody that targets surface receptors overexpressed by cancers.…”
Section: Discussionmentioning
confidence: 99%